AKSELERASI TINGKAT PENGETAHUAN MAHASISWA TENTANG SISTEM DAN PRODUK PERBANKAN SYARIAH MELALUI MEDIA ONLINE PADA PROGRAM STUDI PERBANKAN SYARIAH UIN ALAUDDIN MAKASAR - Trimulato Trimulato (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Sharia banking in Indonesia continues to experience growth, this can be seen from the total assets of sharia banking which has reached 451,202,000,000,000 in 2018. It's just that the market share of sharia banking has not reached 10 percent, but still around 6 percent. The level of public knowledge and literacy about sharia products is also still minimal. Efforts are needed to increase public knowledge and interest in increasing the use of product of sharia banking. Technological advances can be used as a means to increase knowledge about sharia banking system and product. Students are one element that utilizes technology a lot as a medium of learning, especially in increasing knowledge. This research is a field research, which is obtained data through pre-test and post-test activities to 34 students to provide answers to the questions given. This research is qualitative in nature, with direct data collection techniques to student of departement sharia banking UIN Alauddin Makassar. The analysis technique used is descriptive qualitative related to the level of student knowledge and the use of Google classroom in learning. The results of this study show an increase in student knowledge about sharia banking system and product after pre-test and post-test. The average value increase from 78.4 increased to 86.1. The increase in value reached 9.8 percent. Google classroom can be used as a learning medium in the form of providing materials, learning videos, discussions and quizzes. This media can increase the knowledge of sharia banking for students departement of sharia banking UIN Alauddin Makassar about system and product of sharia banking. Keywords: Knowledge, System and Product of Sharia Banking, Online Media, and Students Departement of Sharia Banking UIN Alauddin Makassar.